Violencia de género y protocolos de la Junta Cantonal DeProtección De Derechos Del Cantón Zapotillo, Periodo 2024. - Jaramillo Mendoza, Joselyn Anahí (2024)
Gender violence is a problem that affects a large part of the female population worldwide and nationally, and to address it it is necessary to implement care protocols that allow for comprehensive intervention. The general objective of this research was to analyze the structure of the protocols used by the Cantonal Board for the Protection of Rights of Zapotillo Canton in the attention of cases of gender violence, in order to seek alternative solutions. It was also based on specific objectives focused on describing the structure of the protocols used by the Zapotillo Cantonal Board for the Protection of Rights in dealing with cases of gender violence; to determine to what extent the protocols followed by the Zapotillo Cantonal Board for the Protection of Rights provide the required support; and to design an intervention proposal for dealing with cases of gender violence in the Zapotillo Cantonal Board for the Protection of Rights. In order to fulfill each of the objectives, a qualitative methodology was used with a transversal non-experimental design and the application of instruments such as a semi-structured interview with the total population of five officials of the organization. The results of the research made it possible to identify that the protocols guarantee the effectiveness of the support required by the agency.